Expression of programmed cell death protein 1 and T‐cell immunoglobulin‐ and mucin‐domain‐containing molecule‐3 on peripheral blood CD4+CD8+ double positive T cells in patients with chronic hepatitis C virus infection and in subjects who spontaneously cleared the virus. Issue 8 (29th April 2019) - Caraballo Cortés, Kamila; Osuch, Sylwia; Perlejewski, Karol; Pawełczyk, Agnieszka; Kaźmierczak, Justyna; Janiak, Maciej; Jabłońska, Joanna; Nazzal, Khalil; Stelmaszczyk‐Emmel, Anna; Berak, Hanna; Bukowska‐Ośko, Iwona; Paciorek, Marcin; et al.
Abstract: Chronic hepatitis C virus (HCV) infection is characterized by increased proportion of CD4+CD8+ double positive (DP) T cells, but their role in this infection is unclear. In chronic hepatitis C, immune responses to HCV become functionally exhausted, which manifests itself by increased expression of programmed cell death protein 1 (PD‐1) and T‐cell immunoglobulin‐ and mucin‐domain‐containing molecule‐3 (Tim‐3) on T cells. The aim of our study was to determine PD‐1 and Tim‐3 phenotype of DP T cells in subjects with naturally resolved and chronic HCV infection. Peripheral blood mononuclear cells from 16 patients with chronic infection and 14 subjects who cleared HCV in the past were stained with anti‐CD3, anti‐CD4, anti‐CD8, anti‐PD‐1 and anti‐Tim‐3 antibodies and, in 12 HLA‐A*02‐positive subjects, MHC class I pentamer with HCV NS31406 epitope. In chronic and past HCV infection, proportions of total DP T cells and PD‐1+ DP T cells were similar but significantly higher than in healthy controls. DP T cells were more likely to be PD‐1+ than either CD4+ or CD8+ single positive (SP) T cells. HCV‐specific cells were present in higher proportions among DP T cells than among CD8+ SP T cells in both patient groups. Furthermore, while the majority of HCV‐specific DP T cells were PD‐1+, the proportion of HCV‐specific CD8+ T cells which were PD‐1+ was 4.9 and 1.9 times lower (chronic and past infection, respectively). PD‐1 and Tim‐3 were predominantly expressed on CD4 high CD8 low and CD4 low CD8 high cells, respectively, and co‐expression of both markers was uncommon.